2015
DOI: 10.1038/ncomms7712
|View full text |Cite
|
Sign up to set email alerts
|

Cracks in Martian boulders exhibit preferred orientations that point to solar-induced thermal stress

Abstract: The origins of fractures in Martian boulders are unknown. Here, using Mars Exploration Rover 3D data products, we obtain orientation measurements for 1,857 cracks visible in 1,573 rocks along the Spirit traverse and find that Mars rock cracks are oriented in statistically preferred directions similar to those compiled herein for Earth rock cracks found in mid-latitude deserts. We suggest that Martian directional cracking occurs due to the preferential propagation of microfractures favourably oriented with resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
55
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 57 publications
7
55
0
Order By: Relevance
“…In particular, McFadden, Eppes, Gillespie, and Hallet (), Eppes et al (), and (Eppes et al, ) observed that most crack features in boulders lying in the deserts of Arizona, east United States, Australia, and Mongolia exhibited an N–S orientation, strong circumstantial evidence that these crack features were driven by thermal stresses induced by heating from the sun moving along an E‐W path relative to the boulder. Similar crack feature orientations have be observed by the rovers on Mars (Eppes et al, ). If thermal stress weathering is operative in bodies with atmospheres, then it is very likely more effective on airless bodies where the lack of an atmosphere enables larger diurnal temperature variations and faster rate of temperature change (Jewitt & Li, ).…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…In particular, McFadden, Eppes, Gillespie, and Hallet (), Eppes et al (), and (Eppes et al, ) observed that most crack features in boulders lying in the deserts of Arizona, east United States, Australia, and Mongolia exhibited an N–S orientation, strong circumstantial evidence that these crack features were driven by thermal stresses induced by heating from the sun moving along an E‐W path relative to the boulder. Similar crack feature orientations have be observed by the rovers on Mars (Eppes et al, ). If thermal stress weathering is operative in bodies with atmospheres, then it is very likely more effective on airless bodies where the lack of an atmosphere enables larger diurnal temperature variations and faster rate of temperature change (Jewitt & Li, ).…”
Section: Introductionsupporting
confidence: 80%
“…Despite the fact that these airless bodies experience large diurnal temperature variations (on the order of ∼100 K), thermal stress weathering has long been presumed to be of little significance in the inner solar system. Within the last decade, thermal stress weathering has been revisited with greater rigour and is now suspected to play an important role in rock breakdown, regolith generation, crater degradation, and landscape evolution in Earth's deserts and cold regions (Hall, ; Lamp, Marchant, Mackay, & Head, ), Mars (Eppes, Willis, Molaro, Abernathy, & Zhou, ; Viles et al, ), Mercury (Molaro & Byrne, ), Moon (Mazrouei, Ali Lagoa, Delbo, Ghent, & Wilkerson, ; Molaro, Byrne, & Langer, ; Molaro, Byrne, & Le, ; Ruesch et al, ), near‐Earth asteroids (Delbo et al, ; Dombard, Barnouin, Prockter, & Thomas, ; Graves, Minton, Molaro, & Hirabayashi, ; Jewitt, ), and perhaps comets (Alí‐Lagoa, Delbo, & Libourel, ; El‐Maarry et al, ; Pajola et al, ; Shestakova & Tambovtseva, ; Tambovtseva, Grinin, & Kozlova, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, temperature cycling within rocky substrates is indicative of mechanical stresses that are implicated in both fine-scale and landform-scale geomorphological change (e.g., Aldred et al, 2016;Collins and Stock, 2016;Eppes et al, 2015;Hall and Thorn, 2014;Vasile and Vespremeanu-Stroe, in press). In these respects, organic modulation of thermal regimes (both surface and subsurface) has potential importance for the efficacy of mechanical weathering, topographic change, and material decay (Coombes et al, 2013a).…”
Section: Coastal Rocks and Engineered Structuresmentioning
confidence: 99%
“…Many weathering mechanisms that occur on Earth are hypothesized to have acted on Mars, including salt weathering [e.g., Malin , ; Clark and Hart , ; Rodriquez‐Navarro , ; Jagoutz , ; Head et al , ], insolation or thermal weathering [ McFadden et al , ; Viles et al , ; Eppes et al , ], eolian weathering [e.g., Fenton et al , ; Bridges et al , ; Bourke et al , ; Bishop , ], and chemical weathering, mainly by acidic volatiles after the Noachian [e.g., Burns , ; Banin et al , ; Hurowitz and McLennan , ; Chevrier and Mathé , ]. Moreover, the abundance of fluvial landforms that have been identified on the surface of Mars [e.g., Dickson and Head , ; Carr and Head , ], and the regular occurrence of temperatures below and above the freezing point of water, suggests that freeze‐thaw weathering may have also occurred on Mars.…”
Section: Introductionmentioning
confidence: 99%